Written Language Skills of The Samin Community in Blora - Nendriyani, Munika; Rahmawati, Laili Etika (Universitas Muhammadiyah Surakarta, 2023)
The Samin tribe, a prominent community in Java, constitutes a distinct socio-cultural grouping defined by its unique way of life and communal ethos. Each indigenous community, existing within the framework of village life, manifests distinctive characteristics, notably discernible to outsiders unfamiliar with the intricacies of Samin culture. Geographically dispersed across Java, the Samin tribe finds representation notably in the Blora Regency. Noteworthy among their skills are proficiency in language and writing. Employing qualitative methodology, this study endeavors to capture authentic insights into the language aptitude, particularly in writing, among students belonging to the Samin tribe in Blora Regency. Data collection hinges upon observation and meticulous analysis, focusing on adolescents attending junior high schools in Blora. The overarching objective of this research is to assess the linguistic and writing proficiencies within the Samin tribe community of Blora Regency. The findings and ensuing discourse reveal commendable levels of linguistic and writing proficiency among Samin tribe adolescents, particularly those enrolled in junior high schools. While demonstrating adeptness in writing, albeit occasionally marred by inaccuracies, there remains scope for enhancement within the Samin tribe community. Addressing this need necessitates tailored educational interventions to bolster language and writing competencies. Such initiatives are imperative to ensure the integration and educational parity of the Samin tribe within the broader Indonesian context, wherein language and writing proficiency are pivotal components of academic attainment.